(untitled) (TERRA LATINOAMERICANA, 2024)
High temperature negatively af fects plant growth and crop yield. The aim was to evaluate the ef fect of maximum temperature on yield and water use ef ficiency in forage corn with subsurface drip irrigation and surface irrigation in five consecutive growing seasons (spring and summer) in the comarca Lagunera. The study was carried out at the La Laguna Experimental Field, of the National Institute of Forestry, Agricultural and Livestock Research (INIFAP) in Matamoros, Coahuila. The research was carried out during summer 2019, spring 2020, summer 2020, spring 2022, and summer 2022 growing seasons. The variables were: maximum temperature, plant height, dry forage, water depth, and water use ef ficiency. The highest temperatures were recorded in spring 2022 and the lowest in the summer growing season of the same year. Overall, the highest plant heights occurred in the coolest growing season (summer 2022). A higher yield of dry forage (19 Mg ha-1) was in the 2022 summer growing season. The highest water depth was applied in the spring 2022 growing season (71 cm) and the lowest in summer 2020 (55 cm). This resulted in higher water use ef ficiency in summer. The variation in water use ef ficiency between growing seasons was due to higher temperatures in spring. Finally, water use ef ficiency tended to decrease by 19% as temperature increased from 30 to 38 degrees Celsius.